Tuvan Riddles about Artifacts in a Linguo-Cognitive Aspect - Bochina, Tatyana G. (The New Research of Tuva, 2025)
This article examines the signs of material culture of the Tuvans through the lens of riddles, which are regarded as a kind of dictionary of the folk conceptual sphere and one of the tools for transmitting ethnic culture and socializing new generations. The research is based on 297 riddles about artifacts collected in the anthology of Tuvan riddles compiled by G. N. Kurbatsky, published in 2021. Through the rankings of nominative density and frequency of thematic groups of riddles, as well as the analysis of extensive synonymic series within texts about the same artifact, the author reveals the significance of material spheres of Tuvan culture and identifies the most frequent encoded objects within the enigmatic corpus.The author has established that the most significant existential sphere for the Tuvans is the yurt and its “object” world, especially kitchen utensils — those material signs of culture that, from an early age, surround children, the primary audience for enigmatic texts. The second most represented sphere in the riddles is activity: artifacts of horse breeding, the traditional occupation of the Tuvans, as well as instruments and weapons associated with hunting.The author has identified a pattern: the more recurrent a sphere is in the enigmatic space, the greater the number of riddle-synonyms circulating within it, conveying various features of the guessed objects, and the more multi-member synonymic series of riddles exist. The presence of a series of texts encoding the same artifact allows for the reconstruction of voluminous, multifaceted images of signs of traditional material culture, synthesizing external features, internal qualities, functions of the object, and its correlations with related (accompanying) items.
Keywords: riddle; Tuvans; Tuvan folklore; Tuvan culture; artifact; nominative density